Prognostic role of C-reactive protein to albumin ratio in cancer patients treated with immune checkpoint inhibitors: a meta-analysis - Dai, Menglu; Wu, Wei (Frontiers in Oncology, 2023)
Background: There are numerous articles investigating whether C-reactive protein to albumin ratio (CAR) is significant for predicting prognosis of cancer cases receiving immune checkpoint inhibitors (ICIs), whereas the results were inconsistent. We thus retrieved the literature and conducted the present meta-analysis for clarifying relation of CAR with survival outcomes among ICIs treated cancer patients. Methods: Through search against the Web of Science, PubMed, Cochrane Library and Embase databases was carried out. The search was updated on 11 December, 2022. This work later determined the combined hazard ratios (HRs) together with 95% confidence intervals (CIs) for estimating CAR for its prognostic efficiency for overall survival (OS) and progression-free survival (PFS) in cancer patients receiving ICIs. Results: A total of 11 studies consisting of 1,321 cases were enrolled into the present meta-analysis. As revealed by combined data, the increased CAR level markedly predicted dismal OS (HR=2.79, 95%CI=1.66-4.67, p<0.001) together with shortened PFS (HR=1.95, 95%CI=1.25-3.03, p=0.003) among carcinoma cases using ICIs. The prognostic effect of CAR was not influenced by clinical stage or study center. Our result reliability was suggested by sensitivity analysis. Conclusions: High CAR expression showed marked relation to worse survival outcomes among ICIs treated cancer cases. CAR is easily available and cost-effective, which can be the potential biomarker for selecting cancer cases benefiting from ICIs.